A STUDY ON THE SECOND YEAR STUDENTS’ ABILITY OF SMP TRI BHAKTI PEKANBARU IN COMPREHENDING TEXTS - Dwi Risti Wanti; Rumiri Aruan; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was aimed to find out the ability of the students in comprehending descriptive text, recount text, and narrative text in reading comprehension. This research was conducted at SMP Tri Bhakti Pekanbaru. The try-out class was 8.3 with the number of total 35 students. The sample class was 8.1 with the number of total 32 students. The try-out class and the sample class were chosen by cluster random sampling. The result showed that the ability of the second grade students of SMP Tri Bhakti Pekanbaru in comprehending descriptive text, recount text, and narrative text was fall into good level with the mean score of 61. The students’ highest score was in finding factual information with the mean score of 72.9. On the other hand the lowest score that students got was finding meaning of vocabulary with the mean score of 49. Meanwhile, the other aspects were such as finding main idea with the mean score of 61, finding the reference with the mean score 67.7, finding the inference with the mean score that is 55.2, finding generic structure with the mean score of 63, finding language feature with the mean score of 58.8, and finding the social function with the mean score of 59.3.Key Words: Student’s Ability, Descriptive Text, Recount Text, Narrative Text.